Issues and Challenges for Intelligent Battery Management System in Electric Vehicles - Snehal Shinde (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Background: Electric Vehicle is an emerging sector in the world. In electric vehicles, the battery and battery management system (BMS) are the most essential components. Performance of electric vehicles highly depends on battery management system operations. Issues and challenges in BMS can degrade vehicle’s performance. Methods: We selected about 51 articles having higher relevance factors from the Scopus database. We analyzed 25 articles to study challenges in BMS in detail. In this article, we have addressed the issues and challenges which may affect electric vehicle efficiency. Findings: The challenges like real time state estimation, data security, temperature management, charging-discharging of battery, prediction of battery life, power source availability, disposal issues, etc are most common. These challenges can be considered for enhancing electric vehicle performance. Conclusion: Analysis of issues and challenges in BMS is provided in this paper.